소년원 임시퇴원제도에 대한 정책적·입법적 개선방안 - 김혜정; Kim¸ Hye-jeong (소년보호연구, 2021)
In the Juvenile Act, there is a protective disposition for resocialization from an educational point of view that helps juvenile offenders grow into healthy adults. The reason why we are preparing a juvenile criminal justice policy separately from the criminal justice policy for adults is that we believe that juvenile offenders have a higher potential for education and improvement than adult offenders. It is necessary to help juvenile grow into healthy adults rather than stigmatizing them as criminals and punishing them even if they commit crimes. The Juvenile Reformatory provides education such as subject education, vocational competency development training, and certification exam so that juvenile in protection can be nurtured so that they can return to society as healthy juveniles. Among juveniles detained in Juvenile Reformatory, if it is recognized that the purpose of correction has been achieved because of good correctional grades, they are subject to ‘Release on Parole’ or ‘Release’ pursuant to Article 44 of ‘Act on the Treatment of Protected Juveniles’. Protective juveniles imposed with disposition No. 9 will be ‘Release on Parole’ from the Juvenile Reformatory with about one month remaining. Upon release on parole, the juvenile will be charged with probation for six months. Because of the situation in which they will receive probation for a period that is about six times the remaining period, juvenile in probation often think that release on parole is rather unfavorable treatment. In principle, it is reasonable that the probation imposed along with Release on Parole should be for the remainder of the confinement period. For the judgment of Release on Parole, it is necessary to make a specific evaluation using various currently developed recidivism risk assessment tools. If necessary, it is also necessary to actively review the development of a tool to evaluate the recidivism risk of children in protection.